Internal green marketing orientation and business performance: The role of employee environmental commitment and green organizational identity - Elshaer, Ibrahim Abdelhamid; Azazz, Alaa Mohamed Shaker; Alshebami, Ali Saleh; Abdulaziz, Tamer Ahmed; Mansour, Mahmoud Abohashem; Fayyad, Sameh (International Journal of Innovative Research and Scientific Studies, 2024)
The research examines the idea that Internal Green Marketing Orientation (IGMO) is a strategic approach within the tourism and hospitality industries that focuses on integrating environmentally friendly practices into the organizational culture. It encompasses how a business perceives, values, and prioritizes environmental concerns as part of its internal operations. IGMO, as a fundamental aspect of a company’s strategy, plays a significant role in shaping Business Performance (BP) in this sector. How does IGMO influence Business Performance (BP) in the tourism and hospitality industries, and what is the role of Employee Environmental Commitment (EEC) and Green Organizational Identity (GOI) in this relationship? The purpose of this study is to find the answers to the previous questions. The study randomly gathered data via time-lagged surveys distributed among workers with at least two years of experience in hotels and tourism companies in Egypt. The study employed Partial Least Squares Structural Equation Modeling (PLS-SEM) to analyze the perceptions of 338 employees working in hotels and tourism companies in Egypt. The study’s results showed that IGMO is positively associated with BP. Furthermore, IGMO is positively associated with EEC. In addition, EEC is positively associated with BP. EEC succeeded in mediating the association between IGMO and BP. Finally, the study proved that GOI moderates the association between IGMO and EEC. Practical implications include prioritizing IGMO, fostering employee environmental commitment, recognizing the impact of employee commitment on business performance, leveraging employee commitment as a mediator, and understanding the role of green organizational identity in shaping employee commitment.